Embryo aggregation regulates in vitro stress conditions to promote developmental competence in pigs - Jeong, Pil-Soo (PeerJ, 2019)
Embryo aggregation is a useful method to produce blastocysts with high developmental competence to generate more offspring in various mammals, but the underlying mechanism(s) regarding the beneficial effects are largely unknown. In this study, we investigated the effects of embryo aggregation using 4-cell stage embryos in in vitro developmental competence and the relationship of stress conditions in porcine early embryogenesis. We conducted aggregation using the well of the well system and confirmed that aggregation using two or three embryos was useful for obtaining blastocysts. Aggregated embryos significantly improved developmental competence, including blastocyst formation rate, blastomere number, ICM/TE ratio, and cellular survival rate, compared to non-aggregated embryos. Investigation into the relationship between embryo aggregation and stress conditions revealed that mitochondrial function increased, and oxidative and endoplasmic reticulum (ER)-stress decreased compared to 1X (non-aggregated embryos) blastocysts. In addition, 3X (three-embryo aggregated) blastocysts increased the expression of pluripotency, anti-apoptosis, and implantation related genes, and decreased expression of pro-apoptosis related genes. Therefore, these findings indicate that embryo aggregation regulates in vitro stress conditions to increase developmental competence and contributes to the in vitro production of high-quality embryos and the large-scale production of transgenic and chimeric pigs.